The relationship between some variables with birth outcome among postdate pregnant women delivering at Maternity Teaching Hospital Sulaymaniyah City, Iraq - Mohammed, Atiya K. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Continuation of pregnancy may sometimes be life threatening for the mother and the fetus if the indication is frequently prolonged. Sometimes, it is necessary to bring on labor artificially because of safety concerns for the mother and her baby. A descriptive observational study performed in 200 postdate pregnant women who attended to the delivery room for induction of labor. The Purposive data collection took 3 consecutive months starting from February 28th, 2019 until May 26th 2019. A questionnaire and a checklist were designed for the purpose of the study and Bishop score, APGAR and patient’s chart were used. Content and Face Validity of the instrument was established and the reliability was measured by using Cronbach’s alpha = 0.96. Formula for research, instrument. Descriptive & inferential statistical used for analysis data it was done with the SPSS version 22.0 software. Women’s education, body mass index and method of delivery with mode of delivery had significant association. The overall caesarean section rate in this study was quartered. Half of them had a variety of complications and 44% of newborn needed admission to the neonatal intensive care unit. The rate of cesarean section was higher among participant were induced with misoprostol than who were induced by oxytocin. The statistically no significant relationship between the birth outcome with socio-demographic factors (age, residency, occupation and educational level), gravidity and Bishop score and the mode of delivering was determined in the study
Keywords: Birth outcome; postdate pregnant women; Sulaimani City/Iraq